Situation of the Covid-19 epidemic in patients on peritoneal dialysis on 2020/05/15 in France : RDPLF data-base - Mathilde Nouvier; Christian Verger; Denis Fouque (RDPLF, 2020)
Numerous studies have shown that chronic renal failure, whatever the treatment, is an important risk factor during the SARS-Cov2 pandemic. We present the incidence of COVID-19 infection, and its lethality, in France according to data from the French Language Peritoneal Dialysis Registry (RDPLF), during the period of the epidemic peak between March 1 and May 15, 2020. Of the 3,104 patients treated with PD during this period, from 156 centers, 59 contracted COVID-19, ie 1.8%, a percentage significantly lower than that observed in center hemodialysis. Diabetes was found in 64% of infected patients while it was only present in 36% of uncontaminated patients. The mode of contamination was attributed to a hospital stay in 19% of the cases, a family infection in 17% of the cases, treatment in nursing homes in 15% of the cases, unknown in 44% of the cases. Sixty-two percent of the infected patients were on assisted PD, without identifying the source of contamination. The mortality rate was high at 40%, comparable to other countries in PD. A comparison with hemodialysis could only be made after adjustment for comorbidities and patient profiles: data on hemodialysis are not available in the RDPLF. Home peritoneal dialysis decreases the risk of Covid-19 contamination, but associated comorbidities and age are the source of high mortality. Non-autonomous patients have a higher risk of contamination.